British Association of Urological Surgeons (BAUS) consensus document: Management of female voiding dysfunction. (25th April 2021) - Biers, Suzanne M.; Harding, Chris; Belal, Mo; Thiruchelvam, Nikesh; Hamid, Rizwan; Sahai, Arun; Parkinson, Richard; Barratt, Rachel; Ali, Ased; Reid, Sheilagh; ,
Abstract : Objectives: To report the British Association of Urological Surgeon's (BAUS) guidance on the assessment and management of female voiding dysfunction. Methods: A contemporary literature search was conducted to identify the evidence base. The BAUS Section of Female, Neurological and Urodynamic Urology (FNUU) Executive Committee formed a guideline development group to draw up and review the recommendations. Where there was no supporting evidence, expert opinion of the BAUS FNUU executive committee, FNUU Section and BAUS members, including urology consultants working in units throughout the UK, was used. Results: Female patients with voiding dysfunction can present with mixed urinary symptoms or urinary retention in both elective and emergency settings. Voiding dysfunction is caused by a wide range of conditions which can be categorized into bladder outlet obstruction (attributable to functional or anatomical causes) or detrusor underactivity. Guidance on the assessment, investigation and treatment of women with voiding dysfunction and urinary retention, in the absence of a known underlying neurological condition, is provided. Conclusion: Wa have produced a BAUS approved consensus on the management pathway for female voiding dysfunction with the aim to optimize assessment and treatment pathways for patients.